Zirconium in the Nuclear Industry: Twelfth International Symposium 2000
DOI: 10.1520/stp14314s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Composition and Fabrication Process on Out-of-Pile and In-Pile Properties of M5 Alloy

Abstract: Within the scope of the optimization of the M5 cladding tubes made of ternary alloy (Zr, Nb, O), an extensive program of investigation and industrial development has been undertaken. The various possible factors and potential causes of variability have been thoroughly analyzed with the aid of industrial-scale or laboratory ingots from the point of view of their impact on the finished product properties. In this way, all the chemical composition variabilities of the alloying elements (Nb, O) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 4 publications
3
50
0
1
Order By: Relevance
“…In addition, under agreements among NRC-Studsvik-AREVA and NRC-Studsvik-Westinghouse, high-burnup defueled M5 cladding from the European Ringhals PWR reactor and ZIRLO cladding from the North Anna PWR reactor, respectively, were supplied to ANL for post-quench ductility testing. Cladding materials from these high-burnup rods are characterized in sections (5,6) relevant to the tests conducted.…”
Section: Description Of Cladding Alloys and High-burnup Fuel Segmentsmentioning
confidence: 99%
“…In addition, under agreements among NRC-Studsvik-AREVA and NRC-Studsvik-Westinghouse, high-burnup defueled M5 cladding from the European Ringhals PWR reactor and ZIRLO cladding from the North Anna PWR reactor, respectively, were supplied to ANL for post-quench ductility testing. Cladding materials from these high-burnup rods are characterized in sections (5,6) relevant to the tests conducted.…”
Section: Description Of Cladding Alloys and High-burnup Fuel Segmentsmentioning
confidence: 99%
“…Therefore, the development of advanced Zr alloys for a fuel cladding is being progressed in various countries. [1][2][3] The general properties of industrial materials are dependent on the microstructure of the materials and that of the materials is affected by the chemical composition and manufacturing process. 4) The corrosion kinetics and mechanical properties of a Zr alloy are affected by the alloying element and the precipitates that were formed by adding various alloying elements.…”
Section: Introductionmentioning
confidence: 99%
“…Since the corrosion behavior of a Zr alloy is largely affected by a Nb addition as an alloying element, most of the advanced Zr alloys for a fuel cladding contain Nb to improve their corrosion resistance. [1][2][3] It has been reported that the corrosion behavior of a Nb-containing Zr alloy was very complex depending on the Nb content and annealing condition. [5][6][7] From these reports, it was confirmed that a Nb addition to Zr alloys improved their corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Nb-containing alloys are oxidised faster than recrystallised Zircaloy in oxygen and in water vapour [4,[8][9][10][11][12], at the beginning of the oxidation, but the kinetic transition is not so sharp in Nb-containing alloys and it occurs after a longer time. In autoclave, different results are obtained, these alloys showing in most cases a better resistance to corrosion [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Nb-containing alloys are oxidised faster than recrystallised Zircaloy in oxygen and in water vapour [4,[8][9][10][11][12], at the beginning of the oxidation, but the kinetic transition is not so sharp in Nb-containing alloys and it occurs after a longer time. In autoclave, different results are obtained, these alloys showing in most cases a better resistance to corrosion [14,15].Another difference between the two alloys is related to the effect of platinum on the oxidation rate: if platinum is deposited on the surface of an oxide layer grown on ZrNbO, in pre-transition, the oxidation rate increases, in oxygen [10] or in water vapour [11], whereas Pt has no effect on the oxidation of Zy4 [11,12].Moreover, it has been shown that the oxidation rate depends on the niobium concentration in the zirconium alloy [16], and on the oxygen pressure [17].In order to account for these results, the pre-transition stage of the oxidation of ZrNbO is suggested to be controlled by a mixed diffusion-reaction regime, and therefore in steady conditions [10,13].Finally, due to the lack of consistent data on the effect of water vapour on the oxidation rate before and after the transition, and in order to confirm (or not) these interpretations, we have studied the oxidation of a Nb-containing zirconium alloy, ZrNbO alloy, at 530°C, following the same methodology as in the case of . This approach is principally based on the verification of kinetic assumptions that are usually made a priori.…”
mentioning
confidence: 99%